Atomic-scale pathway of early-stage precipitation in Al–Mg–Si alloys. (1st January 2015) - Fallah, Vahid; Korinek, Andreas; Ofori-Opoku, Nana; Raeisinia, Babak; Gallerneault, Mark; Provatas, Nikolas; Esmaeili, Shahrzad
Abstract: Strengthening in age-hardenable alloys is mainly achieved through nano-scale precipitates whose formation paths from the atomic-scale, solute-enriched entities are rarely analyzed and understood in a directly verifiable way. Here, we discover a pathway for the earliest-stage precipitation in Al–Mg–Si alloys: solute clustering leading to three successive variants of face-centered cubic (fcc) clusters, followed by the formation of non-fcc GP - zones . The clusters, which originally assume a spherical morphology ( C 1 ), evolve into elongated clusters and orient themselves on 111 Al ( C 2 ) and subsequently on 100 Al planes and 〈 100 〉 Al directions ( C 3 ). We also analyze the association of quenched-in dislocations with clustering phenomena. The results of this work can open a new frontier in advancing alloy-process-property design for commercially important age-hardenable Al alloys.